Analisis Dampak Emosional dan Psikologis yang Terbawa dalam Film Hello Ghost (Studi Deskriptif Kualitatif pada mahasiswa Ilmu Komunikasi Universitas Islam Negeri Sunan Kalijaga) - Dwi Utami; Lilis Ernawati; Safira Karimah Aulia (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This research analyzes the emotional and psychological impact experienced by the audience after watching the film Hello Ghost. The movie was released in Indonesia in 2023. Hello Ghost tells the story of Kresna, a young man who wants to commit suicide. However, Kresna fails to kill himself and is instead followed by four ghosts with different characters. The ghosts will not leave unless Kresna grants their wishes. The purpose of this article is to develop readers' knowledge and understanding of the psychological impact experienced by the public on the effects of mass communication in the movie hello ghost. Qualitative research methods were used in this study by collecting information through surveys, questionnaires, and interviews to the target audience of Halo Hantu based on the movie. According to the results obtained from respondents, there are 10 out of 33 people who like this Hello Ghost movie, people who like this Hello Ghost movie, where the majority of the audience are fans of the horror and comedy genres. These two genres have their own elements, both in presenting the work. Therefore, psychological effects work by moving or stimulating the emotions experienced by the audience, and this paper aims to observe the emotional and psychological effects for those who watch this movie. Keywords: Movie, Women, Ghost, Family, Psychologycal.